Avalia????o de impactos cumulativos no planejamento ambiental de hidrel??tricas na regi??o amaz??nica: an??lise a partir dos instrumentos de avalia????o de impacto aplicados na bacia do rio Teles Pires - Silva, Jo??o Carlos da (2017)
The importance of preserving the Amazonian biome given its ecological relevance to the planet does not prevent the concentration of energy projects in the Amazon region due to its unique hydro potential. The hydrographic basins of the Amazon River, which includes the Teles Pires River and the Tocantins River, account for about 80% of the new hydroelectric plants planned to meet the demands of electricity in Brazil according to planning documents. The debate about the significant socio-environmental impacts associated with the advance of the hydroelectric frontier for the Amazon region has been intense. In the country since 2003, the hydroelectric sector, besides having their projects evaluated by the Environmental Impact Studies (EIS), also began to be discussed in the context of watersheds through the Integrated Environmental Assessment (IEA). Given the socio-environmental vulnerability of the Amazon region to the construction and operation of hydroelectric plants, it is relevant to discuss the cumulative impacts resulting from multiple hydroelectric plants in the same basin. The objective of this research is to study the environmental studies carried out in the Teles Pires river basin and three hydroelectric projects in this basin, respectively, the Teles Pires river basin IEA and the Colider Hydroelectric plant EIS, the Teles Pires Hydroelectric plant and the Sinop Hydroelectric plant. Thus, it is established as a research question: How the cumulative impacts of hydroelectric projects inserted in a hydrographic basin in the Amazon region are being analyzed in the environmental planning instruments through the Integrated Environmental Assessment and Environmental Impact Study? The general objective of the research is to analyze the evaluation of cumulative impacts from the Teles Pires river basin scale in the Amazon region to the hydroelectric scale by environmental impact assessment instruments applied to the environmental planning of hydroelectric dams. The results of the research show that there is an association between the cumulative impacts presented in the Integrated Environmental Assessment for the Teles Pires river basin and the Environmental Impact Studies of the uses inserted in this basin. The results also point out that the good practices of Cumulative Impact Assessment are present mainly at the river basin level. It is considered that the cumulative impacts of hydroelectric projects inserted in a hydrographic basin in the Amazon region are being analyzed in the environmental planning instruments, mainly through the Integrated Environmental Assessment of the basin and, to a lesser extent, through the Environmental Impact Study of Hydroelectric use.